Sistem Pengendalian Resiko Gagal Bayar Nasabah Pembiayaan Di BMT Amanah Ummah Surabaya - Toyyibi, Abdul Majid (Program Studi Perbankan Syariah Institut Al-Fithrah (IAF) Surabaya, 2025)
A Sharia financial institution such as BMT Amanah Ummah expects a health in financing its customers, but the running of financing activities certainly emphasizes that the implementation of technical rules that will occur in the event of default problems so that risk control becomes the main thing for BMT analysts. The purpose of this study is to determine the BMT risk control system in the occurrence of the risk of default of financing customers. While this study is a type of field research which then uses qualitative as its research approach. In order to obtain credible results, the researcher carried out data collection techniques, data analysis to the validity of the data. The results of the study are that an analyst of BMT Amanah Ummah prioritizes the principle of prudence as an initial control because it is the main basic part that must be considered in addition to also having to review it based on the character of its customers.